(untitled) (Sciences & Technologie. C, Biotechnologies, 2002)
Polyphenolic compounds and tannins are natural substances of secondary plant metabolism. They are well known for their antinutritional effects. These properties are due to their ability to interact and precipitate protein of the diet. They are responsible for the inhibition of digestion and the decrease of nutritive value of some legumes and cereals grains. Owing to their ability to interact strongly with protein of the ratio, they could be responsible to the inhibition activity of several enzymes [1,2]. So an important particularity must be reserved to these compounds when they are integrated into the diet. Five methods for the measurement of total phenolics, condensed tannins, and tanning capacity of Vicia faba L. were tested for their reliability ; some of them were improved for their sensitivity. The results were interpreted so as to draw the phenolic pattern of each variety of Vicia faba L, and they revealed different cases.